Jam Terbang Dalam Tujuh Hari, Jenis Penerbangan dan Risiko Acute Fatigue Syndrome - Nida Fakhriyyah Rahmah; Pritha Maya Savitri; Agneta Irmarahayu; Suzy Yusna Dewi (WARTA ARDHIA, 2018)
Flight Hours Within Seven Days, Flight Type and Risk of Acute Fatigue Syndrome: Fatigue on pilots is a serious problem in aviation safety. Flight hours and flight types may affect the occurrence of acute fatigue complaints on pilots. This study aims to determine the correlation of total flight hours within 7 days and the type of flight with the Acute Fatigue Syndrome risk on civil pilots in Indonesia. The design of this study used cross sectional method on civil pilots at Civil Aviation Medical Center in December 2017 with consecutive sampling as the sample determination technique. Data were collected by interview and questionnaire methods. Respondents were 112 civil pilots of fixed wing aircraft. The study population was all the pilots who conducted medical examination at Civil Aviation Medical Center in December 2017. The results showed that as many as 65 (58%) respondents experienced Acute Fatigue Syndrome, 110 (98.2%) respondents had flight hours ≤ 30 hours within 7 days, 76 (67.9%) respondents have short haul flight type. The result of bivariate analysis with Chi-Square test showed that there was no significant relationship between flying hours within 7 days (p = 0,509) and acute fatigue syndrome and there was significant relationship between flight type (p = 0,018) and acute fatigue syndrome. Fatigue pada penerbang merupakan masalah serius dalam keselamatan penerbangan. Jam terbang dan jenis penerbangan dapat mempengaruhi timbulnya keluhan kelelahan akut pada penerbang. Penelitian ini bertujuan untuk mengetahui hubungan jumlah jam terbang dalam 7 hari dan jenis penerbangan dengan risiko Acute Fatigue Syndrome pada penerbang sipil di Indonesia. Desain penelitian ini menggunakan metode cross sectional pada penerbang sipil di Balai Kesehatan Penerbangan bulan Desember 2017 dengan teknik penentuan sample yang digunakan adalah consecutive sampling. Data dikumpulkan dengan metode wawancara dan pengisian kuesioner. Responden sejumlah 112 penerbang pesawat sayap tetap. Populasi penelitian adalah semua penerbang yang melakukan medical examination di Balai Kesehatan Penerbangan pada bulan Desember 2017. Hasil penelitian menunjukkan sebanyak 65 responden atau 58% mengalami Acute Fatigue Syndrome, 110 responden atau 98,2% memiliki jam terbang ≤ 30 jam dalam 7 hari, 76 responden atau 67,9% melakukan penerbangan jenis Short Haul. Hasil analisis bivariat dengan uji Chi-Square didapatkan bahwa tidak terdapat hubungan yang bermakan / signifikan antara jam terbang dalam 7 hari (p = 0,509) dengan acute fatigue syndrome serta terdapat hubungan yang bermakna / signifikan antara jenis penerbangan (p = 0,018) dengan acute fatigue syndrome.